2012
DOI: 10.17221/447/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity coefficient, mechanism, and kinetics of different derivatives of flavones and flavanones towards superoxide radical

Abstract: Ahmed S., Shakeel F. (2012). Antioxidant activity coefficient, mechanism, and kinetics of different derivatives of flavones and flavanones towards superoxide radical. Czech J. Food Sci., 30: 153-163.A systematic investigation of the electrochemically generated superoxide radical (O 2•-) has been conducted in the presence of some flavonoids. Cyclic voltammetry was used to generate O 2 •-by reducing the molecular oxygen in DMSO at room temperature. The scavenging of the radical was monitored by the decrease in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 31 publications
(29 reference statements)
2
39
0
Order By: Relevance
“…Such changes suggested that phenolic sulfur-containing compounds, in reaction to the superoxide anion radical, acted as proton donors (that is, Brønsted acids), which was in good agreement with the literature data [26,27].…”
Section: As Shown Insupporting
confidence: 90%
“…Such changes suggested that phenolic sulfur-containing compounds, in reaction to the superoxide anion radical, acted as proton donors (that is, Brønsted acids), which was in good agreement with the literature data [26,27].…”
Section: As Shown Insupporting
confidence: 90%
“…as well as singlet oxygen ( 1 O 2 − ) . Over produced ROS generates oxidative stress which can be reduced through antioxidant . Antioxidants can not only scavenge the ROS in body but can also regulate ROS related enzymes such as radical generating NAD(P)H oxidase and xanthine oxidase (XO) or radical reducing superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) .…”
Section: Introductionmentioning
confidence: 99%
“…This underestimation, comparing to the DPPH result, was probably due to the low ratio of phenolic acids and flavonoids detected at 750 mV in PP extract which is composed mainly of ellagitannins, macromolecules of tannins. These high molecular weight antioxidants (HMWA) are, possibly, not suitable to CV assay than the low molecular weight antioxidants (LMWA) because of high weight (Ahmed & Shakeel, ) (Chevion, Roberts, & Chevion, ). Moreover, Arteaga et al () reported that only antioxidant DPPH assay of LMWA could be correlated with antioxidant CV assay.…”
Section: Resultsmentioning
confidence: 99%